Acute Angle Closure Secondary to Tubercular Choroidal Granuloma. Issue 12 (December 2017) - Kaushik, Sushmita; Singh, Ramandeep; Arora, Atul; Joshi, Gunjan; Sharma, Kusum; Tigari, Basavraj
Abstract : Acute angle closure is usually thought to be secondary to pupillary block, which is relieved by laser iridotomy. Anterior rotation of the ciliary body at the scleral spur following development of an inflammatory ciliochoroidal detachment may result in a presentation of acute angle closure. It is imperative to recognize this condition correctly, because the management is with cycloplegics and anti-inflammatory drugs, which is diametrically opposite to the treatment of primary angle closure. More importantly, it has been reported as a consequence of serious systemic disease such as HIV infection and Vogt Koyanagi Harada (VKH) syndrome. We report a patient who presented to the medical emergency with headache and vomiting and was subsequently found to have acute angle closure in 1 eye secondary to a tubercular choroidal granuloma. This presentation of ocular tuberculosis has not been reported previously.